Zoledronate induces osteonecrosis of the jaw in sheep. Issue 7 (September 2015) - Voss, Pit Jacob; Stoddart, Martin; Ziebart, Thomas; Zeiter, Stephan; Nelson, Katja; Bittermann, Gido; Schmelzeisen, Rainer; Poxleitner, Philipp
Abstract Introduction The treatment of bisphosphonate-related osteonecrosis of the jaw has become routine in maxillofacial hospitals. However, the etiopathology has not yet been fully understood. The aim of this study was to develop a large animal model for medication-related osteonecrosis of the jaw (MRONJ). Material and methods Eight Swiss mountain sheep were randomly assigned into two groups. Group I received 0.075 mg/kg zoledronate (ZOL) intravenously every third week for 16 weeks. After 16 weeks, extraction of the first and second lower left premolar was performed. Group II underwent surgery and no ZOL was administered. After surgery, Group I continued to receive ZOL infusions; after 16 weeks, all animals were euthanized. The jaw bones were investigated macroscopically, radiographically (computed tomography) and histologically. Results Osteonecrosis of the jaw was observed at all extraction sites in all the animals receiving ZOL, and at none of the sites in animals without ZOL. All ZOL-treated animals spontaneously developed exposed bone lesions in the oral cavity at sites where no surgical intervention was performed. CT imaging shows persistent alveolar extraction sockets 16 weeks after surgery in all animals of the ZOL-group, and healed alveolar extraction sockets in non-ZOL-treated animals. Conclusion Sheep treated with ZOL reproducibly demonstrated osteonecrosis of the jaw after tooth extraction, and spontaneous development of exposed bone in the oral cavity at sites where no manipulation was performed. This animal model can be used for further research in the fields of BP-ONJ etiopathology, oral implantology, bone and fracture healing and periodontology.